LITERATION : ACEHNESS SEDATI ONE DAY FOR TEACHER - Sephia Dini Pratiwi Tiwi (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
ABSTRACT This study is a descriptive qualitative method that raises the phenomenon of literacy or habits related to Acehnese culture. This study aims to provide information related to culture that is currently trending and implemented by teachers, especially elementary schools in Aceh. The "One Day with Acehnese Culture" program in elementary schools (SD) is one way to introduce and preserve Acehnese culture to the younger generation. This program usually involves various activities that aim to instill a sense of love and pride in local culture. Elementary school literacy activities are one-day activities for teachers that focus on Acehnese culture, featuring Sedati performances or lessons as part of an initiative to incorporate local traditions into education and literacy programs. The term "Acehnese Literacy" can refer to initiatives or projects that focus on preserving, disseminating, and integrating Acehnese culture, language, and customs into literacy or education programs. This can involve the development of learning materials, storytelling practices, or cultural workshops that emphasize Acehnese identity and heritage.